Sodium-glucose co-transporter-2 inhibitor (SGLT2i) treatment and risk of osteomyelitis: A pharmacovigilance study of the FAERS database - Zhao, Hui; Li, Zi-Ran; Zhang, Qian; Zhong, Ming-Kang; Yan, Ming-Ming; Qiu, Xiao-Yan (Frontiers in Pharmacology, 2023)
Background and purpose: Several clinical trials have indicated that the use of canagliflozin increases the risk of lower extremity amputation. Although the US Food and Drug Administration (FDA) has withdrawn its black box warning about amputation risk for canagliflozin, the risk still exists. We sought to estimate the association between hypoglycemic medications, especially sodium-glucose co-transporter-2 inhibitors (SGLT2is), and adverse events (AEs) before the irreversible outcome of amputation as a promising early warning, based on the FDA Adverse Event Reporting System (FAERS) data. Methods: Publicly available FAERS data were analyzed using a reporting odds ratio (ROR) method and validated by a Bayesian confidence propagation neural network (BCPNN) method. The developing trend of the ROR was investigated by a series of calculations based on the accumulation of data in the FAERS database quarter by quarter. Results: Ketoacidosis, infection, peripheral ischemia, renal impairment, and inflammation including osteomyelitis might be more likely to occur among users of SGLT2is, especially canagliflozin. Osteomyelitis and cellulitis are AEs unique to canagliflozin. Among 2,888 osteomyelitis-related reports referring to hypoglycemic medications, 2,333 cases were associated with SGLT2is, with canagliflozin accounting for 2,283 of these cases and generating an ROR value of 360.89 and a lower limit of information component (IC025) of 7.79. No BCPNN-positive signal could be generated for drugs other than insulin and canagliflozin. Reports suggesting that insulin could generate BCPNN-positive signals span from 2004 to 2021, whereas reports with BCPNN-positive signals emerged only since the second quarter (Q2) of 2017, 4 years since the approval of SGLT2is in Q2 of 2013, for canagliflozin and drug groups containing canagliflozin. Conclusion: This data-mining investigation revealed a strong association between canagliflozin treatment and developing osteomyelitis that might be a crucial forewarning to lower extremity amputation. Further studies with updated data are needed to better characterize the risk of osteomyelitis associated with SGLT2is.